The Effect of Hyperbaric Oxygen Therapy on Functional Impairments Caused by Ischemic Stroke - Emily R. Rosario; Stephanie E. Kaplan; Sepehr Khonsari; Garrett Vazquez; Niyant Solanki; Melanie Lane; Hiriam Brownell; Sheila S. Rosenberg (Neurology Research International)
Background. While research suggests a benefit of hyperbaric oxygen therapy (HBOT) for neurologic injury, controlled clinical trials have not been able to clearly define the benefits. Objective. To investigate the effects of HBOT on physical and cognitive impairments resulting from an ischemic stroke. Methods. Using a within-subject design a baseline for current functional abilities was established over a 3-month period for all subjects (n=7). Each subject then received two 4-week periods of HBOT for a total of 40 90-minute treatments over a 12-week period. Subjects completed a battery of assessments and had blood drawn six times over the 9-month total duration of the study. Results. We found improvements in cognition and executive function as well as physical abilities, specifically, improved gait. Participants reported improved sleep and quality of life following HBOT treatment. We also saw changes in serum levels of biomarkers for inflammation and neural recovery. In the functional domains where improvement was observed following HBOT treatment, the improvements were maintained up to 3 months following the last treatment. However, the physiological biomarkers showed a pattern of more transient changes following HBOT treatment. Conclusions. Findings from this study support the idea of HBOT as a potential intervention following stroke.